Unveiling singlet fission mediating states in TIPS-pentacene and its aza derivatives - Herz, Julia; Buckup, Tiago; Paulus, Fabian; Engelhart, Jens U.; Bunz, Uwe H. F.; Motzkus, Marcus (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2015)
Femtosecond pump-depletion-probe experiments were carried out in order to shed light on the ultrafast excited-state dynamics of triisopropylsilylethynyl (TIPS)-pentacene and two nitrogen-containing derivatives, namely, diaza-TIPS-pentacene and tetraaza-TIPS-pentacene. Measurements performed in the visible and near-infrared spectral range in combination with rate model simulations reveal that singlet fission proceeds via the extremely short-lived intermediate 1TT state, which absorbs in the near-infrared spectral region only. The T1 → T3 transition probed in the visible region shows a rise time that comprises two components according to a consecutive reaction (S1 → 1TT → T1). The incorporation of nitrogen atoms into the acene structure leads to shorter dynamics, but the overall triplet formation follows the same kinetic model. This is of particular importance, since experiments on tetraaza-TIPS-pentacene allow for investigation of the triplet state in the visible range without an overlapping singlet contribution. In addition, the pump-depletion-probe experiments show that the triplet absorption in the visible (T1 → T3) and near-infrared (T1 → T2) regions occurs from the same initial state, which was questioned in previous studies. Furthermore, an additional ultrafast transfer between the excited triplet states (T3 → T2) is identified, which is also in agreement with the rate model simulation. By applying depletion pulses, which are resonant with higher vibrational levels, we gain insight into internal vibrational energy redistribution processes within the triplet manifold. This additional information is of great relevance regarding the study of loss channels within these materials.
Gesehen am 31.08.2020